2015
DOI: 10.3390/toxins7051457
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinase D/Ceramide 1-Phosphate in Cell Survival and Inflammation

Abstract: Sphingolipids are major constituents of biological membranes of eukaryotic cells. Many studies have shown that sphingomyelin (SM) is a major phospholipid in cell bilayers and is mainly localized to the plasma membrane of cells, where it serves both as a building block for cell architecture and as a precursor of bioactive sphingolipids. In particular, upregulation of (C-type) sphingomyelinases will produce ceramide, which regulates many physiological functions including apoptosis, senescence, or cell differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 48 publications
(80 reference statements)
1
28
0
Order By: Relevance
“…Previous studies associate EP receptors with the BBB (McCullough et al, 2004;Pekcec et al, 2009;Jiang and Dingledine, 2013). EP2, in particular, shares biologic characteristics with C1P; both EP2 and C1P have been implicated with decreased apoptosis, increased angiogenesis, and the promotion of inflammatory responses through COX-2 (Sung et al, 2005;Kamiyama et al, 2006;Liang et al, 2008;Kim et al, 2013;Rivera et al, 2015). Our results show that EP2 exists almost exclusively on the luminal membrane of rat brain capillaries, suggesting that in our model PGE 2 activates its receptor in the capillary lumen.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies associate EP receptors with the BBB (McCullough et al, 2004;Pekcec et al, 2009;Jiang and Dingledine, 2013). EP2, in particular, shares biologic characteristics with C1P; both EP2 and C1P have been implicated with decreased apoptosis, increased angiogenesis, and the promotion of inflammatory responses through COX-2 (Sung et al, 2005;Kamiyama et al, 2006;Liang et al, 2008;Kim et al, 2013;Rivera et al, 2015). Our results show that EP2 exists almost exclusively on the luminal membrane of rat brain capillaries, suggesting that in our model PGE 2 activates its receptor in the capillary lumen.…”
Section: Discussionsupporting
confidence: 64%
“…Numerous studies support the antiapoptotic effect of C1P in different cell types. In macrophages and keratinocytes, higher levels of endogenous C1P (after CERK activity upregulation) blocked apoptosis, 12,21 whereas the exogenous addition of C1P to cochlear hair cell and retina photoreceptor cultures also increases cell survival. 13,14 In line with this evidence, we here demonstrated that C1P protects ECFC not only from apoptosis but also from necrosis triggered by 2 molecules highly elevated in the ischemic tissue like TNFα and monosodium urate crystal, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The sphingolipid ceramide has been shown to trigger apoptosis in a wide variety of cells . Ceramide induced cell death involves mitochondria .…”
Section: Introductionmentioning
confidence: 99%